Mental health and access to care among the Roma population in Europe: A scoping review - Guerrero, Zoe; Civišová, Dagmar; Winkler, Petr (Transcultural psychiatry, 2024)
The Roma are Europe's largest ethnic minority group, and often face discrimination and social exclusion. Social strife and lack of access to healthcare are associated with increased symptoms of psychopathology. We aimed to review evidence on mental health outcomes and on access to mental healthcare among the Roma population in Europe. We systematically searched five databases (PsycINFO, Global Health, Social Policy and Practice, Web of Science and PubMed) and conducted a grey literature search in August 2020. We identified 133 studies, 26 of which were included for final analysis. We present the results using a narrative synthesis. The available literature indicates a relatively high prevalence of anxiety, depression and substance abuse among Roma, and females seem to be more affected than males. Roma children exhibit more externalizing and internalizing disorders when compared with non-Roma children. Mental health and perceived well-being among the Roma population are strongly linked to social determinants of health such as housing or economic income. Access to mental healthcare is limited for Roma people because of several barriers pertaining to language, lack of information regarding available services, and the insurance and economic status of Roma people. Roma people report mainly negative experiences with mental health services, including a lack of understanding from healthcare providers, and instances of racism and discrimination. There is a need for more research on mental health and access to healthcare in Roma people. Future studies should be participatory in order to provide guidelines for mental healthcare that addresses the needs of the Roma population.
Keywords: Romové; lidé; mental healthcare; Ethnicity; Female; dítě; Evropa; menšiny; scoping review; Humans; transcultural psychiatry; Health Services Accessibility; mužské pohlaví; dostupnost zdravotnických služeb; duševní zdraví; Roma; Minority Groups; ženské pohlaví; stigma and discrimination; Male; Mental Health; Europe; Child; etnicita